THE ANALYSIS OF THE FINANCE & BANKING STUDENTS’S SKILL IN WRITING DESCRIPTIVE TEXT OF PBI MURNI SADAR - Nora Januarti Panjaitan (Politeknik Bisnis Indonesia, 2018)
This study deals to find out how far the skill of finance & banking students in writing descriptive text. This research was designed as descriptive quantitative research and it was conducted at Indonesian Business Polytechnic which is located in Sriwijaya Street. The number of sample in this research was 25 students which were taken from finance and banking students grade two. In this research, the researcher used writing test as the instrumentation of the research where the students were asked to write a descriptive text based on the topics given to them. In analyzing the students’ writing score, the researcher found that there were 3 students got score in range 85-100 and it can be classified into the excellent level (12%). Then, the researcher found that there were 12 students got score in range 70-84 and it can be classified into the good level (48%). The researcher also found that there were 5 students got score in range 55-69 and it can be classified into the fair level (20 %). Then, the researcher found that there were 3 student got score in range 50-54 and it can be classified into the poor level (12%). Then the last, there are 2 students got score on range 0-49 and it canbe classified into the very poor level (18%). The average score for students’ writing skill in descriptive text in this research was 69.52 and it can be categorized as Fair level. So, it can be concluded that the students writing skill in descriptive text at second grade of finance & banking students Indonesian Business Polytechnic Murni Sadar was in fair level.